(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This study aims to assess the changes in urease and phosphatase activities under a gradient of gypsum content in irrigated gypsiferous soils in the Zarbdor district of Jizzak region. Soil samples were collected from soil profiles with different degrees of gypsum content at depths of 0–15 and 15–30 cm. The gypsum content in the soil was determined using the B.P. Machigin method, while urease and phosphatase activities were measured under laboratory conditions using generally accepted standard biochemical methods. The results showed that increasing gypsum content in the soil was accompanied by a consistent decrease in the activities of both urease and phosphatase. The obtained data confirm that these enzymes can be reliably used as bioindicators for assessing the biological condition of irrigated gypsiferous soils and the degree of development of soil degradation processes.